Electronic structure, carrier mobility and strain modulation of CH (SiH, GeH) nanoribbons. (22nd February 2019) - Zeng, Bowen; Dong, Yulan; Yi, Yougen; Li, Dongde; Zhang, Shidong; Long, Mengqiu
Abstract: Using first-principles calculations coupled with deformation potential (DP) theory, we have systematically studied the band structure, carrier mobility and strain modulation of monolayer graphane (CH), silicane (SiH) and germanane (GeH) nanoribbons. It is found that all the CH (SiH, GeH) nanoribbons are semiconductor with a wide range of band gap. The carrier mobility results show that the armchair germanane nanoribbon (AGeNR) has the characteristic of p -type semiconductor in electrical conduction because its hole mobility is larger than the electron mobility. While the graphane nanoribbon (CNR) behaves as n -type semiconductor in electrical conduction. Compared to AGeNR and CNR, the mobilities of other nanoribbons are much smaller. Moreover, the band structure and carrier mobility of AGeNR and CNR can be effectively tuned by strain. There are different state competing for the valence band maximum (VBM). When the strain exceeds certain value, the VBM is transited to a new band-edge state accompanied with a large increase of hole mobility. The new band-edge state has smaller DP constant because its bond character makes it less sensitive to strain, and thus resulting in higher hole mobility.